2017
DOI: 10.1093/nar/gkx001
|View full text |Cite
|
Sign up to set email alerts
|

Self-cytoplasmic DNA upregulates the mutator enzyme APOBEC3A leading to chromosomal DNA damage

Abstract: Foreign and self-cytoplasmic DNA are recognized by numerous DNA sensor molecules leading to the production of type I interferons. Such DNA agonists should be degraded otherwise cells would be chronically stressed. Most human APOBEC3 cytidine deaminases can initiate catabolism of cytoplasmic mitochondrial DNA. Using the human myeloid cell line THP-1 with an interferon inducible APOBEC3A gene, we show that cytoplasmic DNA triggers interferon α and β production through the RNA polymerase III transcription/RIG-I p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(67 citation statements)
references
References 55 publications
7
59
0
Order By: Relevance
“…Upregulation of APOBEC3 protein expression was previously shown to be dependent on interferon alpha, and it is associated with non-cytolytic clearance of human hepatitis B virus in primary hepatocytes 32 . Cytoplasmic DNA triggers production of type I interferon, leading to massive upregulation of APOBEC3A 33,34 . Here, we investigated the effects of different APOBEC3 proteins, and found that expression of A3C, A3F or A3H limits coronavirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of APOBEC3 protein expression was previously shown to be dependent on interferon alpha, and it is associated with non-cytolytic clearance of human hepatitis B virus in primary hepatocytes 32 . Cytoplasmic DNA triggers production of type I interferon, leading to massive upregulation of APOBEC3A 33,34 . Here, we investigated the effects of different APOBEC3 proteins, and found that expression of A3C, A3F or A3H limits coronavirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…). In the APOBEC3 family, A3B and A3H localize to the nucleus, while A3A and A3G are transiently recruited to the nucleus . When overexpressed, A3B and A3H have been described as a major endogenous source for mutations in various types of human cancer, such as breast, bladder, head and neck, cervical, and lung cancer .…”
Section: Introductionmentioning
confidence: 99%
“…In RNA, where uracil has a coding function, deamination is an RNA editing tool. In DNA, the formation of uracil by APOBEC/AID is a promutagenic lesion which in some cases can be detrimental and cause cancer, but in other cases enables evolution of antibody genes and inactivation of viruses, retroelement, or other cytoplasmic inflammation-inducing DNA [5,11,12].…”
Section: Apobec Family Of Enzymesmentioning
confidence: 99%
“…can deaminate incoming foreign DNA or stress associated cytoplasmic dsDNA released from mitochondria [12,195,196], and this may play a role in modulating dsDNA induced inflammation. Cytoplasmic dsDNA can activate RIG-I inflammatory pathways if it is transcribed into dsRNA by RNA polymerase III [12].…”
Section: Role Of Apobec In Somatic Mutagenesismentioning
confidence: 99%
See 1 more Smart Citation